2022
DOI: 10.3390/s22062202
|View full text |Cite
|
Sign up to set email alerts
|

Initial Study Using Electrocardiogram for Authentication and Identification

Abstract: Recently, several studies have demonstrated the potential of electrocardiogram (ECG) to be used as a physiological signature for biometric systems (BS). We investigated the potential of ECG as a biometric trait for the identification and authentication of individuals. We used data from a public database, CYBHi, containing two off-the-person records from 63 subjects, separated by 3 months. For the BS, two templates were generated: (1) cardiac cycles (CC) and (2) scalograms. The identification with CC was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Biometric recognition uses distinctive physiological and behavioral characteristics to automatically identify individuals. The former characteristics can include the face, fingerprint, iris, and hand geometry, whereas the latter can be gait signature and keystroke [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biometric recognition uses distinctive physiological and behavioral characteristics to automatically identify individuals. The former characteristics can include the face, fingerprint, iris, and hand geometry, whereas the latter can be gait signature and keystroke [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that ECG signals can still be used for authentication purposes even when the signal is distorted by various factors such as motion artifacts, electrode detachment, or changes in heart rate. Pereira et al [ 14 ] investigated the performance of ECG-based authentication when the signal is affected by sudden cardiac events. The authors found that despite the limited data availability caused by sudden cardiac events, ECG-based authentication remains effective.…”
Section: Introductionmentioning
confidence: 99%